Banjuran, Gamelan Prosesi Zaman Bali Kuna - Hendra Santosa; Dyah Kustiyanti; Ida Ayu Wayan Arya Satyani (Mudra Jurnal Seni Budaya, 2022)
This article is part of research entitled "The Evolution of the Balinese Gamelan", which is accompanied by an overview of the changes that occurred after the Gelgel era. This article aims to provide an overview of the Banjuran gamelan form as written in several ancient Balinese inscriptions. Balinese Karawitan experts often associate it with the Balaganjur gamelan, which is now developing in Bali. In order to obtain a comprehensive explanation, this articlewas compiled employing the historical method. The historiography stage in this study was conveyed through the delivery of critical-descriptive analysis. Although the Sukawana A I inscription actually states that Bali's historical era started from 804 AD, the close relationship between Bali and Central Java actually existed around the 7th century, which is proven through various archaeological findings. It certainly opens the suspicion that the Banjuran gamelan image is engraved in the Borobudur Temple’s reliefs. Many asymmetrical shapes of Balinese drums (kendang) are engraved in the reliefs. Furthermore, Balinese drums' shape is also engraved in the Tegawangi Temple’s reliefs in East Java. This form of the Banjuran gamelan is also strengthened by information and data from the Kakawin Nagarakretagama. Gamelan Banjuran is thought to be the forerunner of the development of the Balaganjur gamelan that is currently developing.